Relationship between Placental Pathology and Birth Weight of Newborns at a Tertiary Care Centre in Central Kerala, India: A Cross-sectional Study - Sundar Singh; Dhanya Roy; Latha Abraham; Leela Kamath; Krishna kumar Diwakar (JCDR Research and Publications Pvt. Ltd., 2023)
Introduction: Even minor changes in the placenta are associated with the mortality and morbidity of the growing foetus and mother, which may have long-standing effects on the foetus. Aim: To study the relationship between placental pathological changes and the birth weight of newborn infants. Materials and Methods: In this cross-sectional study conducted at Malankara Orthodox Syrian Church (MOSC) Medical College, Kolenchery, Ernakulam, Kerala, India, over a period of two months, all inborn neonates, irrespective of gestational age, were considered. The first 63 placental samples (with birth weight <2.5 kg) were taken as cases, and the immediately succeeding next 63 were taken as controls (birth weight >2.5 kilograms). At birth, neonatal details including birth weight, gestational age, placental weight, Small for Gestational Age (SGA)/Appropriate for Gestational Age (AGA)/Large for Gestational Age (LGA), etc., were noted. The placentae were carefully removed, weighed before fixation, and subjected to pathological examination (including gross and microscopic examination). Data were analysed using Statistical Package for the Social Sciences (SPSS) version 14.0 software by Chi-square test. Results: A total of 126 placentae were examined. Increased fibrin deposition in the placenta (perivillous, intervillous, or subchorionic) was associated with Low Birth Weight (LBW) neonates (p-value=0.024), but infarcts were not. Increased fibrin deposition in the placenta (p-value=0.016) and infarcts in the placenta (p-value=0.02) were associated with SGA neonates. However, other findings like haemorrhage, thrombus, calcification, metaplasia, necrosis, vasculopathy, infections, fibrosis, vasculitis were not found to be associated with LBW or SGA neonates. There was a moderate positive correlation between placental weight and the birth weight of neonates (r-value=0.59). Conclusion: Abnormal histopathological changes like infarcts and fibrin deposition in the placenta result in LBW infants. Therefore, proper antenatal screening of the mother for immunology-based rejection-like disorders, maternal coagulopathies, and imbalances between angiogenic or antiangiogenic pathways is necessary. Regular follow-up of infants with placental pathological changes are also essential.